Patients treatment with neuroglioma by teniposide and semustine and its influence on Twist and E-cadherin expression - Yongbo Zhang; Guoyi Liu; Meiling Lang; Jing Zhang; Jia Geng (Elsevier, 2016)
This study focuses on curative effects of teniposide combining with semustine on patients with neuroglioma and the influences on the expression of Twist and E-cadherin in tissue. Sixty-eight patients with neuroglioma taking operation in our hospital were divided into two groups randomly. Single radiotherapy was given to 34 patients in group A, and teniposide (VM-26) and semustine (Me-CCUN) were added to radiotherapy for 34 patients in group B. Then, curative effects, survival rate, living quality and adverse reaction rate after operation were compared between two groups. Moreover, the difference in positive expression rate of Twist and E-cadherin before and after treatment between two groups was analyzed by immunohistochemistry. Results: In group B, the effective rate of treatment was 88.2%, and the disease control rate was 70.6%, higher than 52.9% and 32.4% in group A with statistical significance (P < 0.05). Moreover, the survival rate in three years of group B was 44.1%, and the score of living quality was 67.11 ± 4.32, and also higher than 23.5% and 63.79 ± 4.53 in group A with statistical significance (P < 0.05). However, the difference between two groups in adverse reaction rate has no statistical significance (P > 0.05). In addition, the difference in positive expression rate of Twist and E-cadherin between group A and group B has no statistical significance before treatment (P > 0.05). After treatment, however, the positive rate of Twist in group B is lower than that in group A, while the positive rate of E-cadherin is higher. Both differences have statistical significance (P < 0.05). Chemotherapy of VM-26 combining with Me-CCNU can inhibit Twist expression and improve the expression rate of E-cadherin to help improving the curative effects and living quality and increasing survival rate.